2018
DOI: 10.1111/jonm.12599
|View full text |Cite
|
Sign up to set email alerts
|

Evidence based practice readiness: A concept analysis

Abstract: Nurse managers are in the position to address all elements of evidence based practice readiness. Creating an environment that fosters evidence based practice can improve patient outcomes, decreased health care cost, increase nurses' job satisfaction and decrease nursing turnover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 23 publications
0
42
0
6
Order By: Relevance
“…Indeed, achievement of the concept of EBP in nursing practice is complex, requiring acknowledging various core components including organizational readiness, nursing, training, equipping, and the leadership will to support EBP. In fact, Schaefer and Welton () argued that realization of EBP requires organizational readiness. This can be reflected in the form of embracing the need for EBP, providing resources, and providing a conducive environment for EBP to thrive.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, achievement of the concept of EBP in nursing practice is complex, requiring acknowledging various core components including organizational readiness, nursing, training, equipping, and the leadership will to support EBP. In fact, Schaefer and Welton () argued that realization of EBP requires organizational readiness. This can be reflected in the form of embracing the need for EBP, providing resources, and providing a conducive environment for EBP to thrive.…”
Section: Discussionmentioning
confidence: 99%
“…It can be explained by the fact that the top priorities of nurse managers are quality and security, EBP is not listed as priority and they have little time and budgets to implement EBP into practice (Melnyk et al, ). Hence, the implementation of EBP requires much more than the nurses’ belief and attitudes, but rather the personal and organisational readiness, such as the knowledge and skills of EBP, adequate resources and time or financial investment (Schaefer & Welton, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this widespread endorsement for EBP, it has not become the criterion of clinical practice in many institutions (Melnyk et al, ). Researchers suggested that the prerequisites to achieving EBP include attitude towards EBP, understanding and confidence of the EBP process, equipping and leadership support (McSherry, Artley, & Holloran, ; Schaefer & Welton, ). However, the gap between evidence and practice points to the existence of various difficulties in achieving EBP among nurses.…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted with authority figures and stakeholders in the field of fall prevention, across three municipalities in Norway. These respondents were chosen because they were important stakeholders and decision-makers in their respective municipalities; consequently, their perspectives have implications for the delivery of physiotherapeutic services in community-based fall prevention interventions [113]. This suggests that similar perspectives may prevail in other physiotherapeutic settings (at least those that consist of stakeholders and decision-makers who play a role in the Norwegian physiotherapeutic services); however, there may be differences in the extent to which the themes that emerged in the present study are emphasized.…”
Section: Discussionmentioning
confidence: 99%